Social Factors Affecting Religious Institutions in the Maintenance of Peace and Harmony in East Hararghe Zone: The Case of Selected Religious Institutions - Abreham Belachew; Birhanu Midakso (Cogent Social Sciences)
The study investigated social factors affecting the maintenance of peace and harmony by religious institutions in East Hararghe zone of Oromia region. In doing so, the study employed a qualitative research approach as the issue deals with people’s perspectives and lived experiences. Explanatory cross-sectional and case study research designs were employed to uncover the reasons for the inability to maintain peace and harmony and go deep into the selected cases, respectively. The study used key informant interview, in-depth interview, focus group discussion, and published and unpublished documents to gather relevant data. A purposive sampling technique was employed to select informants who have sufficient knowledge in the area. The study employed thematic analysis to sort-out important themes. The findings of the study demonstrated that lack of entertaining ethnolinguistic differences among followers of the religious institutions, lack of good relationship and mutual support between religious institutions, internal divisions within the institutions, lack of knowledge of theology and modern education, capacity, and spiritual integrity by religious fathers, power struggle and lack of trust among religious fathers, and unequal treatment of religious institutions by government as social factors affecting religious institutions in maintaining peace and harmony. The study recommends that religious institutions should entertain ethnolinguistic differences of their followers to the level expected of them. Additionally, the government should treat religious institutions found in the study area equally and entertain their cases officially to maintain peace and harmony successfully.